Researcher Identity in Transition: Signals to Identify and Manage Spheres of Activity in a Risk-Career - Montserrat Castelló; Sofie Kobayashi; Michelle McGinn; Hans Pechar; Jenna Vekkaila; Gina Wisker (EARLI, 2015)
Within the current higher education context, early career researchers (ECRs) face a 'risk-career' in which predictable, stable academic careers have become increasingly rare. Traditional milestones to signal progress toward a sustainable research career are disappearing or subject to reinterpretation, and ECRs need to attend to new or reimagined signals in their efforts to develop a researcher identity in this current context. In this article, we present a comprehensive framework for researcher identity in relation to the ways ECRs recognise and respond to divergent signals across spheres of activity. We illustrate this framework through eight identity stories drawn from our earlier research projects. Each identity story highlights the congruence (or lack of congruence) between signals across spheres of activity and emphasises the different ways ECRs respond to these signals. The proposed comprehensive framework allows for the analysis of researcher identity development through the complex and intertwined activities in which ECRs are involved. We advance this approach as a foundation for a sustained research agenda to understand how ECRs identify and respond to relevant signals, and, consequently, to unravel the complex interplay between signals and spheres of activity evident in struggles to become researchers in a risk-career environment.